Modern's project: bible origins - Mariya Chikarkova (Cхід, 2014)
This paper deals with diachronic of rethink by the philosophy of modern times primordial existential problems of man, come down to European consciousness through their crystallization in the Bible, which was formed in the controversy with the pagan-magical desire to dominate man in the world. Bible ceases to be arch myth-poetical folk stories, it has mainly intellectualists nature and aims to organize reality of life on eradication of mythologist, strengthening a sense of the significance of their own real history of the Jewish people and the nations that surround it as sacrosanct, a cautionary tale. A task knowledge of the laws of the Divine plan and the distinction between Good and Evil places in the centre of the world Deity becomes a breeding ground for Christian anthropocentrism that elevating man as the "image of God", seamlessly connects with theocentric situation, and it is different from anthropocentrism of ancient-Renaissance type, that really treats a person as theomachist and "ruler of nature", which is made later in the project Modern. That is, the latter is already present in the Bible in the "bound" form, and formed, in fact, in the bosom of the biblical worldview. This biblical rational concept was replaced by anthropocentric myth, utopian fantasies, mythologies of "secularized religion", the mythologizing of scientific knowledge and even revival of occultism. This situation makes the view look at the innovation and creativity of the project.